Identification of the optimal points for the acupuncture treatment of neck pain in China: protocol for a multicenter, matched, case-control study - Ling Zhao; Hui Zheng; Mingsheng Sun; Guoyan Geng; Jiao Chen; Xingsha Ma; Mingxi Yan; Dingjun Cai; Fan-rong Liang; Chunxia Yang; Siyuan Tao; Jieru Peng (BMJ Open)
Introduction Neck pain (NP) is a common condition that can be effectively treated by acupuncture. However, several treatment point prescriptions (ie, local acupoints, distal acupoints, and sensitised acupoints) may be used. The present study aims to identify the types of sensitisation and the distribution of sensitised points in patients with NP, to analyse the cut-off values and sensitisation rate for acupoint sensitisation, and to summarise the dominant forms of optimally sensitised points. This information will be helpful when choosing the optimal points to treat NP.Methods and analysis This multicentre, matched, case–control study will enrol 224 patients with NP, and 224 age-matched and sex-matched healthy participants as controls. Body surface temperature, mechanical pain threshold, pressure pain threshold and skin resistance will be assessed at the 15 acupoints most frequently used to treat NP, and at the five body regions in which pain occurs most frequently. Hypothesis testing will be used to compare the differences in variables between cases and controls. In addition, receiver operating characteristic curve analysis will be used to explore the cut-off values of the sensitive states of heat, pain and electrical resistance, which indicate sensitisation of the acupoint. The optimal points will be comprehensively determined by the acupoint sensitisation rate and OR.Ethics and dissemination Ethical approval of this study has been granted by the Research Ethical Committee of the Teaching Hospital of Chengdu University of Traditional Chinese Medicine (ID: 2018 KL-016). The outcomes of the study will be disseminated through peer-reviewed publications.Trial registration ChiCTR1800016220.